Imaging modalities in diagnosis and treatment monitoring of head and neck non-adrenal paragangliomas - Grzesiakowska, Urszula; Smorczewska, Malwina; Olszewski, Michał (Contemporary Oncology/Współczesna Onkologia, 2009)
The aim of this study was to define the role of imaging techniques in detection of paragangliomas of the head and neck and follow-up of patients treated with radiation therapy. Material and methods: 20 patients aged between 24 and 75 were diagnosed by CT and MR (both examinations were performed before and after contract administration). Patients had follow-up every 4-6 months for first 2 years and then usually once a year. The follow-up periods was between 1 and 7 years. Results: we detected 29 paragangliomas, in that 13 jugolothympanic tumors and 16 carotid body tumors, 4 patients have multifocal lesions, 8 lesions were operated, in these cases the diagnosis was established by microscopic examination. Biopsy gave no conclusive results. The remaining 12 patients were diagnosed on the basis of clinical and radiological studies. 14 patients were treated by radiation therapy. In the follow-up of one case we detected progression. Conclusions: Our study suggested that diagnosis of paragangliomas could be made through clinical examination and radiological imaging. Both methods are equal for monitoring therapy and follow-up.